Characterization of environmental liabilities: the Colombian case - Pereira Bolaños, Cliden Amanda; Ariza Ruiz, Efren Danilo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The descriptive research shows the environmental liabilities generated by the mining activity in the city of Bogotá, Colombia. The qualitative approach allows identifying the areas dedicated to the mining activity of extraction, exploitation and production of materials for construction in the city; For this, a documentary review and observation work were carried out to know the current state of the environmental impact generated by this activity in the south of the city. The results show an advance of the ongoing investigation where the environmental liabilities generated by mining in the south of Bogotá can be identified.